Ukraine’s policy in Afghanistan - K Petrovich Kurylev (RUDN Journal of World History, 2013)
The article investigates the process of evolution of Ukraine’s foreign policy in Afghanistan. The author determines the national interests of Ukraine in this state and describes the main stages of cooperation in political, military and economic spheres. The current issue is considered on the basis of the analysis of a number of Ukraine’s doctrines in the field of foreign policy and national security. The author concludes that the relations between Ukraine and Afghanistan don’t contain any contradictions, which could have a negative impact on their development.